Очень тонкая сталь - Самаров Сергей Васильевич (Спецназ ГРУ, 2017)
Экземпляры: аб. ЦБ (20181017) / Инвентарный номер: 5322 / Цена: / Сис.шифр: 84(2Рос=Рус) / Авт.знак: С 17 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)